2016
DOI: 10.2147/dddt.s122984
|View full text |Cite
|
Sign up to set email alerts
|

Development of docetaxel nanocrystals surface modified with transferrin for tumor targeting

Abstract: The purpose of this study was to develop the surface modification of docetaxel nanocrystals (DTX-NCs) with apo-Transferrin human (Tf) for improving the cellular uptake and cytotoxicity of DTX. DTX-NCs were prepared by a nanoprecipitation method, and the surface modified with Tf by an adsorption method (Tf-DTX-NCs). The morphology and particle size of DTX-NCs and Tf-DTX-NCs were characterized using a field emission scanning electron microscope and zetasizer. An in vitro drug release study was performed in phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…101,102 A few representative examples of active tumor targeting using various nanocarriers surface modified with site-specific ligands are described here. In a study, Choi and Park 103 reported the development of docetaxel-loaded nanocrystals having surface modification with transferrin to endow them with active tumor-targeting function. Transferrin-modified docetaxel nanocrystals exhibited higher cellular uptake and cytotoxicity in human lung A549 cancer cell line as compared to docetaxel nanocrystals and pure drug.…”
mentioning
confidence: 99%
“…101,102 A few representative examples of active tumor targeting using various nanocarriers surface modified with site-specific ligands are described here. In a study, Choi and Park 103 reported the development of docetaxel-loaded nanocrystals having surface modification with transferrin to endow them with active tumor-targeting function. Transferrin-modified docetaxel nanocrystals exhibited higher cellular uptake and cytotoxicity in human lung A549 cancer cell line as compared to docetaxel nanocrystals and pure drug.…”
mentioning
confidence: 99%
“…A previous study has demonstrated that the surface modification of NPs can improve the effect of active targeting and reduce drug adverse reactions to the normal cells 33. Increasing evidence from multiple studies has shown that Tf, TfR, and their biological significance have been widely characterized 34. Sinha et al reported that an upregulation of TfR level was detected in tumor cells compared to normal cells,10 which may be related to the increased expression of TfR.…”
Section: Discussionmentioning
confidence: 99%
“…Active cancer-targeting utilizes the attaching targeted moieties for better delivery of nanoparticle systems to the tumor site [55]. Active targeting takes advantage of the highly expressed surface receptors on cancer cells by keeping them engaged with the targeting ligands.…”
Section: Active Cancer Targetingmentioning
confidence: 99%